Dyslexia and dysgraphia of primary progressive aphasia in Chinese: A systematic review - Liu, Junyan; Ota, Shoko; Kawakami, Nobuko; Kanno, Shigenori; Suzuki, Kyoko (Frontiers in Neurology, 2022)
Introduction Currently, little is known about Chinese-speaking primary progressive aphasia (PPA) patients compared to patients who speak Indo-European languages. We examined the demographics and clinical manifestations, particularly reading and writing characteristics, of Chinese patients with PPA over the last two decades to establish a comprehensive profile and improve diagnosis and care. Methods We reviewed the demographic features, clinical manifestations, and radiological features of Chinese-speaking PPA patients from 56 articles published since 1994. We then summarized the specific reading and writing errors of Chinese-speaking patients. Results The average age of onset for Chinese-speaking patients was in their early 60's, and there were slightly more male patients than female patients. The core symptoms and images of Chinese-speaking patients were similar to those of patients who speak Indo-European languages. Reading and writing error patterns differed due to Chinese's distinct tone and orthography. The types of reading errors reported in Chinese-speaking patients with PPA included tonal errors, regularization errors, visually related errors, semantic errors, phonological errors, unrelated errors, and non-response. Among these errors, regularization errors were the most common in semantic variant PPA, and tonal errors were specific to Chinese. Writing errors mainly consisted of non-character errors (stroke, radical/component, visual, pictograph, dyskinetic errors, and spatial errors), phonologically plausible errors, orthographically similar errors, semantic errors, compound word errors, sequence errors, unrelated errors, and non-response. Conclusion This paper provides the latest comprehensive demographic information and unique presentations on the reading and writing of Chinese-speaking patients with PPA. More detailed studies are needed to address the frequency of errors in reading and writing and their anatomical substrates.